EQUALITY, THE CONSUMER PROTECTION ACT AND CUSTOMER-SEGMENT PRICING STRATEGIES: IS THERE RELIEF FOR THE POOR RICH TOURIST? - Mark Tait; Madéle Tait (Obiter, 2021)
The year 2010 is Soccer World Cup year in South Africa. From watching the press and other media it quickly becomes apparent that this event is perceived as something of a cash cow to be used (and sometimes even abused) to generate maximum profit for certain industries and its businesses. Complaints have been made about airlines and accommodation establishments hiking prices excessively. The tourism industry has been warned about the negative impact such exorbitant prices may have on tourism in the future as South Africa may no longer be considered as a value-for-money destination. The hiking of prices is based on an anticipated increase in demand for certain services and products caused by the expected influx of soccer tourists. Businesses world-wide employ different pricing strategies to try and optimize revenue. One such pricing strategy that is employed is to differentiate between citizens and foreign nationals when charging for a service or product. This strategy in the context of the tourism industry is the focus of this note. Whilst the tourist is visiting South Africa s/he may want to visit some attractions and it is often at these places that an interesting situation can be observed. International tourists have to pay one price whereas citizens pay a reduced price. For instance, a visit to the website of the Addo Elephant National Park reveals that SANParks asks different prices – for South African citizens and residents R30 per day visit, SADC nationals R60 per day visit, and foreign visitors R130 per day visit to the Addo Elephant National Park. Similar price differentiation is employed by private businesses as well. Other jurisdictions in Africa also make use of similar customer-segment pricing strategies. The Ugandan Wildlife Authority differentiates between admission fees for foreign non-residents and East-Africans to protected areas such as Lake Mburo and the Semuliki National Park. The Consumer Protection Act 68 of 2008 (hereinafter “the CPA”), once operational, will prohibit the charging of different prices for any goods or services to any persons or category of persons on the basis of one or more of the grounds of unfair discrimination contemplated in section 9 of the Constitution of the Republic of South Africa, 1996 (the Constitution) or Chapter 2 of the Promotion of Equality and the Prevention of Unfair Discrimination Act 4 of 2000 (hereinafter “the Equality Act”), amongst others. Does this mean that suppliers of services and products to tourists who differentiate in the prices asked between citizens and non-citizens will fall foul of this provision of the CPA? This is the question this note will endeavour to answer.